ANALISIS KESULITAN BELAJAR MAHASISWA DALAM PEMBELAJARAN DARING PADA MATA KULIAH STATISTIKA - Kartikasari, Raras (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2023)
The research was carried out with the aim of analyzing difficulties in the student learning process in online learning in Statistics courses. This research was conducted using a descriptive qualitative method. Descriptive qualitative research has several stages as follows: data collection, data reduction and drawing conclusions on research data. The research was conducted at the Indonesian Technocrat University. The research subjects were Students of the Mathematics Education Study Program 2021 Class A who were taking an online Statistics course. Based on the description of the research results, it can be concluded that the difficulties in the student learning process in Statistics courses which are carried out online are influenced by internal factors and external factors. Learning difficulties from internal factors include: difficulties in motivation and interest in learning and difficulties in understanding the material. Learning difficulties influenced by external factors, namely: difficulties in understanding lecturer explanations, signal difficulties and data quotas owned by students, difficulties in using learning applications, limited gadgets owned and difficulties in obtaining support for the learning environment.